FRI0258 Decreased tslp expression in labial salivary glands of patients with primary sjögren's syndrome is associated with increased t and b cell inflammation and tissue destruction. (23rd January 2014) - Hillen, M. R.; Kruize, A. A.; Bikker, A.; Wenting-van Wijk, M.; Radstake, T. R.; Lafeber, F. P.; Hack, C. E.; van Roon, J. A.
Abstract : Background: Thymic Stromal Lymphopoietin (TSLP) is a potent immunomodulatory cytokine involved in Th2-mediated immune responses and homeostatic T-cell expansion. Reduced TSLP expression by intestinal epithelial cells was recently shown to lead to reduced Th2 responses and development of Th1-mediated experimental colitis. In addition, TSLP is described as a proinflammatory factor in rheumatoid arthritis, which is driven by Th1/Th17 responses. A Th1/Th17 polarized environment is also present in the salivary glands of patients with Primary Sjögren's syndrome (pSS). Objectives: To investigate TSLP expression in salivary glands of pSS patients as compared to non-SS Sicca (nSS) patients and to study the relationship to local and systemic disease parameters as well as diffusely infiltrating lymphocytes. Methods: Tissue sections of minor salivary glands from 38 pSS and 18 nSS patients were stained with a monoclonal antibody (mAb) against human TSLP or an isotype control. In addition, sections were stained with mAbs against CD3, CD19 and epithelial cell marker cytokeratin high molecular weight (CK HMW) or stained with alcian blue to detect mucus production. The number of TSLP-expressing cells was quantified and expression was correlated to local- and systemic disease parameters. Results: TSLP was almost exclusively expressed by acinar cells in both pSS and nSS patients. The number of TSLP-expressing cells per mm 2 was significantly decreased in pSS patients as compared to nSS patients (462 ± 42 vs. 773 ± 84, p<0.01) and correlated negatively to ESSDAI (r= -0.36, p=0.023), LFS (r= -0.48, p<0.001), ESR (r= -0.41, p<0.01), serum IgG levels (r= -0.41, p<0.01) and positively to the percentage of local IgA producing plasma cells (r= 0.35, p<0.05). At sites with intact, functional epithelium TSLP expression tended to be reduced in pSS patients as compared to nSS patients (965 ± 49 vs. 813 ± 59, p= 0.084). In conjunction to TSLP expression at these sites, the numbers of diffusely infiltrating B- and T-lymphocytes were quantified. Numbers of diffuse infiltrating lymphocytes were increased in pSS patients as compared to nSS patients (829 ± 78 vs. 391 ± 74, p<0.0001) and correlated to TSLP expression quantified at these sites (r= -0.572, p<0.0001). Conclusions: TSLP expression is reduced in pSS patients, associated with local and systemic inflammatory markers including increased lymphocytic infiltration. In addition, decreased TSLP expression in intact epithelial tissue is associated with increased numbers of diffuse infiltrating lymphocytes. Considering the described role of TSLP in promoting Th2 responses at mucosal sites, we hypothesize that TSLP is constitutively expressed in salivary glands and promotes a protective Th2 milieu, whereas loss of TSLP expression contributes to loss of tolerance and Th1/Th17 associated immunopathology in pSS. Disclosure of Interest : None Declared